Developing school laboratory activities design by utilizing android-based digital applications in savanna ecosystem of Ranca Upas - Alfyn Abdan Nurahman; Solikhah Isti Fadilah; Raditha Putri Cahyani; Nabilla Hadistia; Nurul Faizah Siregar (University of Muhammadiyah Malang, 2024)
Smartphone utilizing in learning was widely implemented in the digital technology era. This research aims to utilize Android-based digital applications to develop laboratory activity designs in the savanna ecosystem of the Ranca Upas, Ciwidey, West Java. The descriptive method was used to analyze the quality of existing laboratory activity design and develop alternative laboratory activity design to support student practicum. The reconstruction explanation was carried out following the stages analyze, create, try, and reconstruct (ANBUCOR). The initial stage involved analyzing laboratory activity design from the aspects of curriculum, competence, practicality, and knowledge construction. The pilot test showed that the Android digital application provided clear and systematic guidance for students in laboratory activities, with features for measuring abiotic factors, species identification, and observation notes. Based on the feasibility analysis according to the Vee diagram. Laboratory activity design is classified as feasible but requires adjusting the objects identified in the procedure and leading questions with focus questions. Final reconstruction was conducted based on the test team's feedback and Vee diagram analysis. The results showed that the application made the practical learning more interactive and improved students' understanding of the savanna ecosystem. The revised laboratory activity design serves as an effective reference for teachers and students in out-of-class laboratory activities.